Prevalence of microvascular dysfunction and association with clinical outcomes in heart failure with preserved ejection fraction. (25th November 2020) - Arnold, J; Kanagala, P; Budgeon, C.A; Jerosch-Herold, M.J; Singh, A.S; Khan, J.N; Gulsin, G.S; Squire, I.B; Ng, L.L; McCann, G.P
Abstract: Introduction: Heart failure with preserved ejection fraction (HFpEF) accounts for approximately 50% of symptomatic heart failure. A recently proposed paradigm for the pathophysiology of HFpEF postulates a central inflammatory aetiology with coronary microvascular function at its core. However, the pathophysiological and clinical significance of microvascular dysfunction in HFpEF remains uncertain. Purpose: Utilising cardiovascular magnetic resonance (CMR), we sought to (1) quantify coronary microvascular function, (2) evaluate the impact of microvascular dysfunction and fibrosis on long-term clinical outcomes and (3) examine the relationship between myocardial perfusion and fibrosis. Methods: In a prospective, observational study, 147 subjects (104 HFpEF without a prior history or CMR evidence of coronary artery disease, and 43 asymptomatic controls) underwent multiparametric CMR, comprising left ventricular volumetric assessment, absolute quantitation of myocardial blood flow [MBF] during adenosine stress (140mcg/kg/min) and at rest, and evaluation of diffuse myocardial fibrosis (extracellular volume [ECV]). The primary endpoint was the composite of death or hospitalisation with heart failure. Results: 104 HFpEF patients (mean age 73±9 years, mean ejection fraction 56%) and 43 controls (mean age 73±5 years, mean ejection fraction 58%) were studied. There was no significant difference in resting MBF (1.10±0.42ml/min/g in HFpEF subjects vs 1.00±0.38 ml/min/g in controls, p=0.23), though hyperaemic MBF was lower in HFpEF subjects (1.66±0.68 ml/min/g vs 1.97±0.59 ml/min/g, p=0.01). Myocardial perfusion reserve [MPR] was also lower in HFpEF subjects (1.73±0.75 vs 2.22±0.76; p<0.01). Microvascular dysfunction (defined as MPR<2.0) was present in 70% of HFpEF patients (versus 33% of controls, p<0.01). During median follow-up of 3.4 years, there were 46 composite events. MPR was predictive of clinical outcome (one unit increase – hazard ratio [HR] 0.57; 95% CI 0.35–0.92; p=0.02), as was ECV (one standard deviation [SD] increase – HR 1.65; 95% CI 1.14–2.39; p=0.01). However, there was no significant linear correlation between MPR and diffuse fibrosis (r<0.01, p=0.99). Conclusion: Microvascular dysfunction is highly prevalent in HFpEF and is associated with adverse clinical outcomes. The lack of correlation between abnormal myocardial perfusion and fibrosis challenges the assertion of a direct causal link between these entities. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): NIHR, BHF